Predictors of Stature Concerns among Young Chinese Women and Men - Sun, Qingqing (Frontiers in Psychology, 2017)
Stature concerns are a prominent source of body dissatisfaction for Chinese teenagers and young adults, yet little is known about the psychological factors that account for it. Therefore, this study examined social cultural model and objectification theory as explanations for stature concerns in a sample of undergraduate men and women from a university in Henan, China. Given height is a salient physical attribute for Chinese adolescents and young adults, we extended past studies on objectification theory by adding separate measures for stature surveillance. Participants (231 men, 473 women) completed a questionnaire assaying measures of sociocultural model features (appearance pressure from mass media and close interpersonal networks, appearance social comparisons), objectified body consciousness (body surveillance, body shame, stature surveillance), and stature concerns. In multiple regression models for each gender, appearance pressure from the mass media and stature surveillance were robust predictors of stature concerns for both genders, independent of reported height. Body surveillance predicted stature concerns for women but not men. These findings contribute to the broader field of multicultural body image research and may help to account for specific culturally-salient appearance concerns within samples of young Chinese women and men.